The Oxford Handbook of International Psychological Ethics 2012
DOI: 10.1093/oxfordhb/9780199739165.013.0019
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Issues and Ethics Reviews in Social Science Research

Abstract: Although the ethics of social science research has not enjoyed as much scholarly attention as the ethics of biomedical research, social scientists continue to debate the relevance of research ethics and ethics review to social science research. Like social scientists, biomedical scientists have also objected to ethical review of biomedical research, and much has been gained from the ensuing debates. This chapter reviews much of this recent debate, and proposes the application of a framework developed by Emanue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
101
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(103 citation statements)
references
References 68 publications
0
101
0
Order By: Relevance
“…Autonomy relates to the rights a participant has to make decisions without any negative repercussions (Wassenaar, 2006). The children who formed the participant group were young and within the vulnerable population.…”
Section: Autonomymentioning
confidence: 99%
See 2 more Smart Citations
“…Autonomy relates to the rights a participant has to make decisions without any negative repercussions (Wassenaar, 2006). The children who formed the participant group were young and within the vulnerable population.…”
Section: Autonomymentioning
confidence: 99%
“…This ethical principle compels the researcher to maximise the benefits of the participants who take part in the study (Wassenaar, 2006). Although there was no direct benefit to the children in the study, the researcher ensured that any children identified as having a speech or language difficulty were referred to the appropriate health professional(s).…”
Section: Beneficencementioning
confidence: 99%
See 1 more Smart Citation
“…At the beginning of the therapy process, written and signed informed consent was obtained from the CEO of the Creative Learning Centre as well as from the mothers before carrying out any research. This protected the participants, as well as the facility and ensured respect for the dignity of all persons involved (Wassenaar, 2006). The research does not provide the names of any person partaking in the research, ensuring their confidentiality and anonymity.…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…Confidentially and anonymity of participants was adhered to during the research process (Wassenaar 2006). Group members agreed to respect one another and to keep all personal information discussed in the group confidential.…”
Section: Ethical Considerationsmentioning
confidence: 99%